Evaluating a structured expert elicitation approach for adaptive conservation management based on lessons from five years in practice - Helen J. Mayfield; James Brazill‐Boast; Mick Andren; Michiala Bowen; Adam Fawcett; Trent Forge; Luke Foster; Ross Goldingay; Paul Hillier; Meagan Hinds; Simon Lee; Erica Mahon; et al. (Conservation Biology, 2026)
Adaptive management of threatened species relies on having ex ante estimates of species’ responses to different interventions. Structured expert elicitation is often used to generate these estimates, but comparisons of these expert‐predicted outcomes with observed results are rare. This study aims to evaluate the utility of expert elicitation for adaptive management in the New South Wales Saving our Species program in Australia by revisiting six species management plans that were generated from tailored structured elicitation guidelines developed five years prior. Each species’ management plan included a defined scope, conceptual model, monitoring indicators, and estimated response to management curves under different scenarios. Experts reviewed the conceptual models after five years of management and compared the predicted response to management with observed monitoring data. In three of the six case studies, observed outcomes closely matched predictions. Where predictions diverged, factors such as unanticipated new threats and unexpected responses to interventions potentially contributed to discrepancies. However, in all cases, the structured approach provided a clear logic for planning, enabling managers to systematically refine their understanding. The conceptual models and response curves were valuable for collaborating, communicating, and generating hypotheses for unexpected results. This work demonstrates the value of tailored guidelines in supporting adaptive management processes and showcases the value of documenting expert knowledge in management settings with high uncertainty.

Convection-permitting climate simulations using SINGV-RCM and WRF over the Maritime Continent - Venkatraman Prasanna; Srivatsan V. Raghavan; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Nguyen Ngoc Son; Bhenjamin Jordan Lozada Ona; Pavan Harika Raavi; Anupam Kumar; Jianjun Yu; Chen Chen; et al. (Climate Dynamics, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Evaluating SINGV ‐ RCM for Long‐Term High‐Resolution Climate Simulations Over Southeast Asia - Venkatraman Prasanna; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Xin Rong Chua; Chen Chen; Jian Jun Yu; Pavan Harika Raavi; Fei Luo; Muhammad Eeqmal Hassim; Sandeep Sahany; et al. (International Journal of Climatology, 2025)
Long‐term convection‐permitting dynamical downscaling has been carried out over Southeast Asia and the Western Maritime Continent, using the Singapore Regional Climate Model (SINGV‐RCM) at 8 and 2 km spatial resolutions, respectively. SINGV‐RCM is forced with ERA5 reanalysis data for 36 years (1979–2014) at 8 km resolution over Southeast Asia (79E‐160E; 16S‐24N) with a regular update of the sea surface temperature at 6‐h intervals. Subsequently, the 8 km domain simulation is used for forcing a smaller domain over the Western Maritime Continent at a resolution of 2 km (93E‐110E; 7.2S‐9.9N) for 20 years (1995–2014). Rainfall characteristics including the diurnal cycle, monthly annual cycle, and daily extremes over land and ocean from the two simulations are evaluated against the high‐resolution IMERG precipitation data available from 2001 to 2014. SINGV‐RCM captures mean and extreme rainfall well; however, there are noticeable biases in the rainfall magnitude over the Ocean. These biases agree with the earlier publications on convection‐permitting simulation over the maritime Continent. Models' skill is further evaluated in terms of mean, bias, pattern correlation and RMSE for 8 and 2 km simulations against the IMERG precipitation data.

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

SINGV-RCM: the convection-permitting regional climate model for Singapore - Venkatraman Prasanna; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Xin Rong Chua; Claudio Sanchez; Chen Chen; Jianjun Yu; Harika Pavan Raavi; Fei Luo; Muhammad Eeqmal Hassim; et al. (Climate Dynamics, 2024)
The development of the Singapore regional climate model (SINGV-RCM) is documented in this study. The model’s skill in predicting mean and extreme rainfall over the Maritime Continent at 8 km and 2 km grid resolution is assessed using observed rainfall. The model’s sensitivity to vertical grid and convection parametrization is also evaluated. Results demonstrate the added value of downscaling to 8 and 2 km. The spatial and temporal characteristic of the diurnal rainfall is shown to be in good agreement with the observation. The model also demonstrates skill in capturing extreme rainfall. In general, the rainfall in the 8 km and 2 km simulations are quite similar, when regrided to a coarser resolution. Even then, the convection-permitting simulation at 2 km is found to add value over the 8 km simulation, particularly in capturing the higher rainfall thresholds. Mean biases over the ocean is found to be larger than that over the land, which suggests the need to further tune SINGV-RCM for long climate simulations.

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Hemodynamics in Idealized Stented Coronary Arteries: Important Stent Design Considerations - Susann Beier; John Ormiston; Mark Webster; John Cater; Stuart Norris; Pau Medrano-Gracia; Alistair Young; Brett Cowan (Annals of Biomedical Engineering, 2016)

Erratum to: Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2015)

Identification and characterisation of 17 polymorphic candidate genes for response to parasitic nematode (Trichostrongylus tenuis) infection in red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; Stuart B. Piertney (Conservation Genetics Resources, 2015)

A transcriptomic investigation of handicap models in sexual selection - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; François Mougeot; Jesús Martínez-Padilla; Stuart B. Piertney (Behavioral Ecology and Sociobiology, 2013)

Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2012)

Characterising functionally important and ecologically meaningful genetic diversity using a candidate gene approach - Stuart B. Piertney; Lucy M. I. Webster (Genetica, 2010)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Renal perfusion dynamics during preservation - Stephen W. Flax; John G. Webster; Stuart J. Updike; David T. Uehling (Annals of Biomedical Engineering, 1978)